2014
DOI: 10.1063/1.4886219
|View full text |Cite
|
Sign up to set email alerts
|

Li4FeH6: Iron-containing complex hydride with high gravimetric hydrogen density

Abstract: Li4FeH6, which has the highest gravimetric hydrogen density of iron-containing complex hydrides reported so far, is synthesized by hydrogenation of a powder mixture of iron and LiH above 6.1 GPa at 900 °C. In situ synchrotron radiation X-ray diffraction measurements reveal that while kinetics require high temperature and thus high pressure for the synthesis, Li4FeH6 is expected to be thermodynamically stable slightly below room temperature at ambient pressure; further synthetic studies to suppress the kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Saitoh et al, reported that high temperature at around 900 C was necessary to obtain a high purity Li 4 FeH 6 in order to accelerate the reaction kinetics. 7) Hydrogen pressure higher than 6 GPa pressure was required to avoid subsequent decomposition of Li 4 FeH 6 during synthesis. Although the sample is not a single phase, the quality was good enough for the FTIR to access the hydrogen atomic motion in Li 4 FeH 6 .…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Saitoh et al, reported that high temperature at around 900 C was necessary to obtain a high purity Li 4 FeH 6 in order to accelerate the reaction kinetics. 7) Hydrogen pressure higher than 6 GPa pressure was required to avoid subsequent decomposition of Li 4 FeH 6 during synthesis. Although the sample is not a single phase, the quality was good enough for the FTIR to access the hydrogen atomic motion in Li 4 FeH 6 .…”
Section: Synthesismentioning
confidence: 99%
“…7). The pellet, encapsulated in a pyrolytic boron nitride reaction capsule, was loaded together with a hydrogen source AlH 3 12,13) into a NaCl capsule with a diameter of 1.5 mm and a height of 3.5 mm.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, novel Li 4 FeH 6 (6.7 mass%) was synthesized by hydrogenation of a mixture of LiH and Fe powders at high temperatures and high pressures, on the basis of the theoretical prediction of first-principles calculations. 5,6) Thus, owing to the high hydrogen density, Li 4 T H 6 has potential as a hydrogen storage material.…”
Section: Introductionmentioning
confidence: 99%